2020
DOI: 10.17129/botsci.2622
|View full text |Cite
|
Sign up to set email alerts
|

Does access to natural environments explain differences in the use of wild plants between rural and urban populations?

Abstract: Background: The use of wild plants depends on a number of sociocultural and ecological factors, such as the ease of access to natural environments. This limitation for urban inhabitants leads to differences in the knowledge and use of wild plants compared to rural inhabitants. Hypothesis:  Rural and urban populations tend to share a similar knowledge of plants and use similar plants species when easy access to natural landscapes is available. Study site and years of study: Rural and urban area of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…In SPT, inhabitants speaking an original language were scarce (1.97 %), and there was a lower percentage of households lacking drainage and using charcoal and firewood as fuel in comparison with SAN (Table 1). Traditional SPT medicine has been enriched with introduced species that grow in home gardens, which guarantees immediate access (Cordero et al 2020). People from SPT employed almost the same percentage of introduced and native plants for medicinal use (48 vs. 52 %, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In SPT, inhabitants speaking an original language were scarce (1.97 %), and there was a lower percentage of households lacking drainage and using charcoal and firewood as fuel in comparison with SAN (Table 1). Traditional SPT medicine has been enriched with introduced species that grow in home gardens, which guarantees immediate access (Cordero et al 2020). People from SPT employed almost the same percentage of introduced and native plants for medicinal use (48 vs. 52 %, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Even today, many cultures worldwide still maintain the tradition of gathering wild plants due to their relevance to human survival and well-being ( Toledo et al 2009 , McCarter and Gavin 2015 ). However, despite its importance, traditional knowledge on the use of plants is progressively eroding due to several sociocultural and ecological processes, such as economic globalisation, cultural homogenisation and environmental degradation ( Cordero et al 2020b ). Nowadays, old traditions of plant gathering are being lost in most countries ( Łuczaj et al 2012 ); thus, it is crucial to increase efforts to safeguard traditional knowledge and preserve biological and cultural diversity for future generations ( Asfaw 2009 , Cordero et al 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Although knowledge is acquired mainly through parents and community members ( Turreira-García et al 2015 ), other less traditional sources of information have also been identified. Online resources, such as digital books and websites, are essential for knowledge acquisition, especially in urban contexts, where interaction with nature is limited by multiple factors ( Cordero et al 2020b ). In a highly globalised world, easy access to ethnobotanical data through public websites is an alternative that has been scarcely explored, but could revitalise local identity and traditions ( Menendez-Baceta et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wild edible plants are an important component of urban floras (Díaz-Betancourt et al 1999). Wild edible plants are defined as species that grow spontaneously in self-sufficient populations in natural or disturbed ecosystems and can exist independently of direct human action (Heywood 1999, Cordero et al 2020). These species have been considered as a potential contributor to human diets (Guil-Guerrero et al 1998, Guil-Guerrero 2001, Penafiel et al 2011, Romojaro et al 2013, Turan et al 2003.…”
mentioning
confidence: 99%
“…These species have been considered as a potential contributor to human diets (Guil-Guerrero et al 1998, Guil-Guerrero 2001, Penafiel et al 2011, Romojaro et al 2013, Turan et al 2003. Will edible plants consider native and naturalized species (including weeds and ruderal plants), as well as domesticated species that scape cultivation and can grow without human interaction (Cordero et al 2020). Generally wild edible plants in urban areas are alien species (Díaz-Betancourt et al 1999, Ladio & Rapoport 2002, Tardío 2010, Turner et al 2011) that show tolerance to the stressful conditions imposed by urban environments.…”
mentioning
confidence: 99%